Aroma volatile profiles of thai green chili paste (nam prig noom) preserved by ultra-high pressure, pasteurization and sterilization - A. Apichartsrangkoon (2018)
Volatile components of untreated, pressurized, pasteurized and sterilized Thai green chili paste (Nam Prig Noom) were extracted by solid phase microextraction (SPME) and identified by gas chromatography-mass spectrometry (GC-MS). The chromatograms showed that sulfide compounds such as diallyl sulfide, allyl methyl disulfide and allyl methyl trisulfide in untreated Nam Prig Noom were the largest group among all quantified volatiles, and their increases were mostly enhanced by thermal processes. Besides sulfides, other compounds generated by heat included 3-methyl-2(5H)-furanone, 2-hexyl-5-methyl-[2H]-furan-3-one, 2-methyl-tetradecane and 1,2-dimethyl cycohexane. Most desirable esters and sulfides such as 2-methylbutanoate, 4-methylpentanoate and diallyl sulfide were greatly retained in pressurized products, while an undesirable volatile from Maillard reaction such as 2-hexyl-5-methyl-[2H] -furan-3-one disappeared after pressurization. In addition, benzaldehyde was present with the highest amount among various aldehydes. Besides benzaldehyde, other volatiles diminished under processing including aldehyde class, ester class (methyl salicylate and 4-methylpentanoate), acid class and hydrocarbon class (limonene, 2-methyl tridecane and alpha-longipinene). Some volatiles were relatively stable in all treatments such as 3,4-dimethylthiophene, methyl propyl disulfide, alpha-himachalene and gamma-himachalene. © All Rights Reserved.